CSI, crime scene investigation. The complete eleventh season [videorecording (DVD)] - Szmanda, Eric; Eads, George, 1967-; Fox, Jorja; Fishburne, Laurence, III, 1961-; Helgenberger, Marg; Guilfoyle, Paul; Langham, Wallace (Paramount Home Entertainment, 2011)
A team of forensic investigators are on the case 24/7, scouring the scene, collecting the irrefutable evidence, and finding the missing pieces that will solve the mystery. Features 22 gripping episodes, commentary, featurettes, deleted scenes, and more.